2018
DOI: 10.1148/radiol.2018180273
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI Findings Predict Pathologic Response in Neoadjuvant Treatment of Breast Cancer: The ACRIN 6698 Multicenter Trial

Abstract: Purpose To determine if the change in tumor apparent diffusion coefficient (ADC) at diffusion-weighted (DW) MRI is predictive of pathologic complete response (pCR) to neoadjuvant chemotherapy for breast cancer. Materials and Methods In this prospective multicenter study, 272 consecutive women with breast cancer were enrolled at 10 institutions (from August 2012 to January 2015) and were randomized to treatment with 12 weekly doses of paclitaxel (with or without an experimental agent), followed by 12 weeks of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
219
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 223 publications
(239 citation statements)
references
References 31 publications
14
219
1
5
Order By: Relevance
“…Previous studies in patients undergoing NAC have reported significant changes in tumor ADC with treatment response, with effect sizes generally large compared with our repeatability value of wCV = 4.8%. Responders exhibited tumor ADC increases ranging from 9% to over 60% in the prior studies, depending on treatment timepoint …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies in patients undergoing NAC have reported significant changes in tumor ADC with treatment response, with effect sizes generally large compared with our repeatability value of wCV = 4.8%. Responders exhibited tumor ADC increases ranging from 9% to over 60% in the prior studies, depending on treatment timepoint …”
Section: Discussionmentioning
confidence: 91%
“…The primary MRI technique for assessing breast cancer is dynamic contrast‐enhanced (DCE) imaging, which characterizes tissue vascularity. However, growing evidence supports diffusion‐weighted imaging (DWI), a functional imaging technique reflecting water diffusion properties in tissue, as a supplemental and/or alternative technique to DCE . Specifically, the apparent diffusion coefficient (ADC) measured by DWI reflects water mobility impeded by cellular constituents and interstitial tortuosity, and it has shown promise as an imaging biomarker to measure early tumor response to cytotoxic treatment …”
mentioning
confidence: 99%
“…In previously published results of the ACRIN 6698, the authors explored the combination of ADC, FTV, and HR/HER2 subtype at mid‐NAC. A model combining percentage change in ADC, percentage change in FTV, and cancer subtype resulted in an AUC of 0.71.…”
Section: Discussionmentioning
confidence: 99%
“…The ACRIN (American College of Radiology Imaging Network) 6698 trial, a substudy of I‐SPY 2, evaluated the change in tumor ADC for predicting pCR. The trial found that after 12 weeks of therapy (between drug regimens), the percentage change in tumor ADC predicts pCR . Their study also showed that ADC achieved higher predictive performance in hormone receptor (HR)‐positive and human epidermal growth factor receptor 2 (HER2)‐negative cancer than other cancer subtypes.…”
mentioning
confidence: 99%
“…Functional tumor volume, a computer estimate of volume using a signal enhancement ratio method (signal intensities on pre‐ vs post‐contrast images), was shown to be associated with recurrence‐free survival. Partridge et al, reporting on diffusion‐weighted MRI performance for 242 I‐SPY 2 patients enrolled in ACRIN 6698, observed that combining tumor molecular subtype with changes in the mid‐treatment apparent diffusion coefficient were moderately predictive of pCR (area under the curve = 0.72; 95% confidence interval [CI]: 0.61, 0.83).…”
Section: Discussionmentioning
confidence: 99%